Of spandex and software. (Economist, 1996)
Michael Cowpland is recreating the software package WordPerfect to challenge Microsoft in its most profitable business, the market for office “suites”—usually a word-processor, spreadsheet, database, and graphics program that work together. This market is currently dominated by Microsoft's Office package. Cowpland thinks that he can do better because of two innovations. The first involves launching a new version of WordPerfect using all of the hard-sell marketing tactics of Corel, Cowpland's company. Cowpland's boldest move, however, is a technical one. He is working extremely hard on a version of the WordPerfect suite in Java, the Internet's exciting new programing language. The advantage of Java is that it can run on all types of computer.